2019
DOI: 10.1101/619700
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunodietica: A data-driven approach to investigate interactions between diet and autoimmune disorders

Abstract: Autoimmunity is on the rise around the globe. Diet has been proposed as a risk factor for autoimmunity and shown to modulate the severity of several autoimmune disorders. Yet, the interaction between diet and autoimmunity in humans remains largely unstudied.Here, we systematically interrogated commonly consumed animals and plants for peptide epitopes previously implicated in human autoimmune disease. A total of fourteen species investigated could be divided into three broad categories regarding their content i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In addition, the enhanced immune responses from uveitis patients to the 3 antigens compared with healthy controls indicate the pathogenic potential of food antigens. Similarly, a data-driven approach found that pigs shared unique epitopes with 40 immune-mediated diseases, including Behcet’s disease [68]. The study revealed that food is a vast library of self-antigens, and taking advantage of bioinformatics approaches to find more dietary autoimmune epitopes is vital for eliminating self-antigens from diet of uveitis patients.…”
Section: Tobacco Smoking and Immune-mediated Uveitismentioning
confidence: 99%
“…In addition, the enhanced immune responses from uveitis patients to the 3 antigens compared with healthy controls indicate the pathogenic potential of food antigens. Similarly, a data-driven approach found that pigs shared unique epitopes with 40 immune-mediated diseases, including Behcet’s disease [68]. The study revealed that food is a vast library of self-antigens, and taking advantage of bioinformatics approaches to find more dietary autoimmune epitopes is vital for eliminating self-antigens from diet of uveitis patients.…”
Section: Tobacco Smoking and Immune-mediated Uveitismentioning
confidence: 99%